2020
DOI: 10.1039/d0ma00082e
|View full text |Cite
|
Sign up to set email alerts
|

Covalent attachment of chitosan to graphene via click chemistry for superior antibacterial activity

Abstract: Chemically converted graphene sheets are functionalized by treatment with aryl diazonium salts via click chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…[160] Another type of antibacterial nanocomposite could be obtained by using chitosan equipped with an aryldiazonium group to modify graphene sheets. The resulting assembly showed efficient antimicrobial activity, particularly against S. dysentiriae, [161] opening the door to a host of new possibilities to fight against microbes. Table 1 summarizes the various diazonium salt functionalized nanomaterials described in this review, and their potential applications.…”
Section: Antibacterial Properties Of Nps Functionalized By Diazonium Saltsmentioning
confidence: 99%
“…[160] Another type of antibacterial nanocomposite could be obtained by using chitosan equipped with an aryldiazonium group to modify graphene sheets. The resulting assembly showed efficient antimicrobial activity, particularly against S. dysentiriae, [161] opening the door to a host of new possibilities to fight against microbes. Table 1 summarizes the various diazonium salt functionalized nanomaterials described in this review, and their potential applications.…”
Section: Antibacterial Properties Of Nps Functionalized By Diazonium Saltsmentioning
confidence: 99%
“…An alternative method allowing for the functionalization of graphene with a polysaccharide was recently (2020) described by Huang et al [ 50 ]. In this approach, chitosan ( 1 ) after N-propargylation ( 14 ) was reacted to para -nitrobenzyl azide ( 15 ) by employing CuAAC click chemistry ( Figure 7 ).…”
Section: Covalent Conjugation Of (Poly)saccharides To Graphenementioning
confidence: 99%
“…The reactivity of aryldiazonium salts towards graphene [ 51 , 52 , 53 ] is well-known and it enables the final fixation of the pre-clicked polysaccharide scaffold. In terms of properties, it was found that the graphene-based final material exhibited an improved antimicrobial activity when compared to chitosan itself [ 50 ].…”
Section: Covalent Conjugation Of (Poly)saccharides To Graphenementioning
confidence: 99%
“…Graphene materials are widely regarded as among the most promising options for high-performance devices due to their exceptional electrical conductivity, thermal conductivity, and mechanical stability. Various GO-based composite films, papers, foams, and sponges have demonstrated excellent performance in the context of wearable pressure sensors. However, limited by GO’s inherent poor dispersion, poor processability, and monofunctionality, endowing GO-based pressure sensors with high sensitivity to small and large deformations to meet the growing demand for high sensitivity versatility and wide range testing requirements remains a great challenge. Consequently, the chemical modification of graphene to enhance its dispersion, processability, and multifunctionality has emerged as an appealing approach to broaden its practical applicability.…”
Section: Introductionmentioning
confidence: 99%